Intervención del terapista respiratorio en paciente masculino de 50 años con neumonía adquirida en la comunidad. - Pérez Lozano, Ariel Snaider (2022)
Pneumonia is pathology of common infectious origin that is produced by different types of microorganisms such as bacteria, viruses and more frequently fungi, it produces different signs and symptoms among which we find Dyspnea, tachycardia, pain when breathing and productive cough with secretions. There are several types of pneumonia, among which we find community-acquired pneumonia, which is the subject to be discussed in this case study of a 50-year-old male patient who currently lives in a nice neighborhood with a pathological history of pneumonia. in his adolescence in which increased the infection. Examinations are performed, X-rays in which it is determined diagnosed with community-acquired pneumonia infection also presented in adults and children.